PS8:170 Lupus nephritis in a multi- ethnic cohort of patients with systemic lupus erythematosus from berkshire, uk. (21st March 2018) - Gindea, S; Williams, S
Abstract : Background: Previous studies suggest that ethnicity influences the clinical phenotype in systemic lupus erythematosus (SLE), with lupus nephritis (LN) being more frequent in non-Caucasians. However, there are scarce data regarding prevalence of LN in South-Asian population (Indians, Pakistani, Sri Lanka, or Bangladeshi). Objectives: This study aimed to compare the prevalence of LN between lupus patients of different ethnicities, and to compare demographics and disease characteristics between LN patients. Methods: This is a retrospective chart review study of 100 lupus patients followed from 2013 to 2017 at Wexham Park Hospital, a large district hospital in Southern England. The patients were categorised into four ethnic groups Caucasians, South-Asians, Blacks and Others (mixed race, Orientals, Arabs). LN prevalence, demographic and clinical data were compared using Fisher/Chi-Square tests for categorical variables and Wilcoxon test for continuous variables. Results: Of 100 patients in the study sample, 51% were Caucasians, 31% were South-Asians, 11% were Blacks and 7% had other ethnicities. Mean age was 48 yo and 90% were females. Prevalence of LN was 26% in the full study sample and 24%, 16%, 64% and 57%, respectively, among Caucasians, South-Asians, Blacks and Others. LN prevalence was significantly lower in Caucasians vs Blacks (p=0.01), South-Asians vs Blacks (<0.01) and South-Asians vs Other (p=0.02). Among patients with LN, mean age was lower in South-Asians and Blacks, than Caucasians and Others (44 and 45 yo vs 52 and 51 yo). Blacks appear to include more males (43% vs <25% in the other groups). Renal biopsy, available for 22/26 LN patients, suggested Class II predominance in Caucasians (44% vs 33% in the other groups). Proliferative LN (Class III and IV) was confirmed in 7 patients, without significant predominance in any ethnic group. Specific lupus autoantibodies (anti-dsDNA Ab and/or antiSm Ab) were found in 64% Caucasians, 75% south-Asians, 86% Blacks and 75% others with LN. Conclusion: In our cohort, prevalence of LN in South-Asians was lower than in Blacks, but not statistically different comparing with Caucasians. However, South-Asians and Blacks with LN were younger than Caucasians. These results should be re-examined in larger similar multi-ethnic cohorts.